High-Sensitivity Temperature Sensor Based on Polarization Maintaining Fiber Sagnac Loop - Laipeng Shao (Photonic Sensors, 2018)
Abstract A high-sensitivity all-fiber temperature sensor based on a Sagnac interferometer is demonstrated by splicing a section of polarization maintaining fiber (PMF) between two sections of standard single mode fibers (SMFs). In this sensor, the SMF-PMF-SMF structure in the Sagnac loop is bent into a circle to enhance the sensitivity. The length and curvature of the PMF in the loop are investigated and can be optimized to further increase the temperature sensitivity of the sensor. Results show that the radius of the circle has an important effect upon temperature sensitivity due to the bend-induced birefringence variation of the PMF. The SMF-PMF-SMF structure bent into a circle with a radius of 30 mm exhibits a high-sensitivity temperature of 1.73 nm/°C. The sensor is provided with the advantages of easy fabrication, low-insertion loss, and high sensitivity, which may find potential applications in the field of high precision temperature measurement.